In-situ synthesize of Ag NPs/SiO2 nanocomposite by gamma ray and its application as catalyst in decolorization of dyes - M. Bagherzadeh; M.H. Choopan Dastjerdi; J. Mokhtari; F. Abadian-Naeini; M. Mohsennia (Cleaner Chemical Engineering)
Herein, Ag nanoparticles (Ag NPs) on the surface of nano silica (SiO2), Ag NPs/SiO2, were synthesized in-situ from Ag+ solution by using gamma radiation within a research reactor via a simple method. To accomplish this, a radiation cell was designed and manufactured close to the reactor's core. The cell was designed to allow gamma radiation to samples without neutron collisions and prevent the samples from becoming radioactive. After ensuring that the suspension samples received at least 25 kGy, the synthesized Ag NPs/SiO2 nanocomposite was separated, washed, and dried. Samples of Ag NPs/SiO2 were characterized using XRD, FE-SEM, and EDXA methods to ensure their successful synthesis. The FE-SEM images of nanocomposite showed that the cubic Ag NPs with mostly 100 ± 4 nm particles size, had successfully formed and were well dispersed on the SiO2 surface. After that, the efficiency of the prepared Ag NPs/SiO2 nanocomposite in catalyzing the decolorization reduction reaction of methylene blue (MB), Congo red (CR), and methyl orange (MO) dyes in the presence of NaBH4 was investigated. The results showed that the Ag NPs/SiO2 nanocomposite catalysts completely decolorized MB and reduced the reaction time to 7 minutes. It also catalyzed the complete destruction of CR and reduced the time to 4 minutes and 20 seconds.